(untitled) (Historia, 2021)
Contrary to the usual way of approaching conferences of this nature, historians as well as subject advisors and professionals from several other fields, had to organise them selves within a matter of days to be able to join in or/and officially participate in the South A frican History Project (SAHP) conference held in Rondebosch from 2-5 October 2002. The Ministry of Education and numerous parliamentarians co-operated in presenting the event. Some who attended the conference were fortunate to be financially supported whilst others had to rely on the charity of their respective institutions or societies to assist, whereas others simply were not able to make it owing to a lack of funding or other obligations. Approximately 210 participants attended the conference. Whatever the logistical scenario of each participant or absentee, the conference, superbly organised by the Com pany Conxti ons, was otherwise held in style and in essence a continuation of the 2001 Conf erence by the Ministry of Education, significantly entitled: ‘Saam trek, values , education and dem ocracy in the 21 st Century’.